Gut microbiome as a target organ in diagnosis and treatment of neuropsychiatric disorders and diseases (a literature review) - V. V. Minukhin; O. V. Knysh; L. A. Zhdamarova; H. M. Bolshakova; Yu. V. Voida (Zaporožskij Medicinskij Žurnal)
The aim: analysis of literature data concerning the study on the relationship between changes in the composition, metabolic activity of the intestinal microbiota and the development of neuropsychiatric disorders and diseases.